Association between maternal outdoor physical exercise and the risk of preterm birth: a case-control study in Wuhan, China - Miao Cai; Bin Zhang; Rong Yang; Tongzhang Zheng; Guanghui Dong; Hualiang Lin; Steven E. Rigdon; Hong Xian; Leslie Hinyard; Pamela K. Xaverius; Echu Liu; Thomas E. Burroughs; et al. (BMC, 2021)
Abstract Background China had the second largest proportion of preterm birth (PTB) internationally. However, only 11% of pregnant women in China meet international guidelines for maternal physical activity, a significantly lower proportion than that in Western countries. This study aims to examine the association between outdoor physical exercise during pregnancy and PTB among Chinese women in Wuhan, China. Methods A case-control study was conducted among 6656 pregnant women (2393 cases and 4263 controls) in Wuhan, China from June 2011 to June 2013. Self-reported measures of maternal physical exercise (frequency per week and per day in minutes) were collected. Adjusted odds ratios were estimated using Bayesian hierarchical logistic regression and a generalized additive mixed model (GAMM). Results Compared to women not involved in any physical activity, those who participated in physical exercise 1-2 times, 3-4 times, and over five times per week had 20% (aOR: 0.80, 95% credible interval [95% CI]: 0.68-0.92), 30% (aOR: 0.70, 95% CI: 0.60-0.82), and 32% (aOR: 0.68, 95% CI: 0.59-0.78) lower odds of PTB, respectively. The Bayesian GAMM showed that increasing physical exercise per day was associated with lower risk of PTB when exercise was less than 150 min per day; however, this direction of association is reversed when physical exercise was more than 150 min per day. Conclusion Maternal physical exercise, at a moderate amount and intensity, is associated with lower PTB risk. More data from pregnant women with high participation in physical exercise are needed to confirm the reported U-shape association between the physical exercise and risk of preterm birth.